Effect of Steep Meridian Clear Corneal Incisions in Phacoemulsification. Issue 5 (September 2015) - Song, Wenjun; Chen, Xiaoyong; Wang, Wei
Purpose: To evaluate the torque and flattening effect of steep meridian clear corneal incisions on cornea in phacoemulsification when posterior cornea surface measurements were considered. Methods: Thirty-six eyes underwent cataract surgery with steep meridian clear corneal incisions. Before surgery and at 1 month and 3 months after surgery, corneal topography was measured with a rotating Scheimpflug camera. Both preoperative and postoperative corneal astigmatism were calculated in 2 ways: total corneal astigmatism and keratometric astigmatism. Polar analysis was used to evaluate the flattening and torque effect of steep meridian incisions on corneal astigmatism. Results: Total corneal astigmatism changed significantly after 3 months (p = 0.005) and univariate analysis revealed a significant change 0.25D ± 0.36 D in astigmatic polar value AKP(+45) of total corneal astigmatism (p = 0.047). A decrease in AKP(+0) was observed in both keratometric and total astigmatism at 1 and 3 months, although the decreases were not statistically significant (p = 0.394, p = 0.442, p = 0.602, p = 0.503, respectively). Conclusions: Steep meridian incision performed on the preoperative steeper meridian of keratometric astigmatism may cause a significant torsional effect on total corneal astigmatism as well as reducing the astigmatism along the meridian.